Clinical profile and outcome of patients with rheumatoid arthritis and abnormally high aortic stiffness. (November 2016) - Cioffi, Giovanni; Viapiana, Ombretta; Ognibeni, Federica; Dalbeni, Andrea; Orsolini, Giovanni; Adami, Silvano; Gatti, Davide; Fisicaro, Maurizio; Tarantini, Luigi; Rossini, Maurizio
Objectives: Ascending aorta has an increased stiffness (AoSI) in rheumatoid arthritis (RA) patients due to their chronic inflammatory status. We assessed prevalence and factors associated with increased AoSI and its prognostic role in a large cohort of RA patients. Methods: We prospectively analysed 226 RA patients without overt cardiac disease compared with 226 non-RA patients matched for cardiovascular risk factors (non-RA controls). Abnormally high AoSI was diagnosed if AoSI > 6.07% (95th percentile of the AoSI detected in our reference healthy population). AoSI was assessed at the level of the aortic root by two-dimensional guided M-mode evaluation as part of a thorough echocardiography performed in all patients. Results: AoSI was significantly higher in the RA patients than non-RA controls (6.3 ± 4.5% vs . 4.6 ± 3.5%, p  < 0.001); it was related to older age, higher systolic blood pressure and RA disease. Predictors of AoSI in RA patients were older age, higher systolic blood pressure and the non-prescription of non-steroidal anti-inflammatory drug and/or immunomodulatory/anti-cytotoxic agents. Abnormally high AoSI was diagnosed in 41% RA patients and 21% non-RA controls ( p  < 0.001). The RA phenotype with abnormally high AoSI was a > 60 years old subject with systolic blood pressure > 129 mmHg, mitral annular calcification who was not receiving non-steroidal anti-inflammatory drug. By multivariate Cox regression analysis abnormally high AoSI independently predicted death or all-cause hospitalization (hazard ratio 2.85 (95% confidence interval 1.03–7.85)) at 12-month follow-up. Conclusions: Increased AoSI is common, can be predicted by an ordinary clinical assessment and is a strong predictor of adverse clinical outcome at mid-term follow-up in patients with RA.